MO393ACUTE RENAL REPLACEMENT THERAPY IN CRITICAL ILL OCTOGENARIAN OR OLDER PATIENTS: PROGNOSTIC FACTORS AND RENAL OUTCOMES. (29th May 2021) - Del Risco, Jimena; Casals, Joaquim; Hermida-Lama, Evelyn; Quintana, Luis F; Blasco, Miquel; Piñeiro, Gaston; Poch, Esteban; Molina Andujar, Alicia
Abstract: Background and Aims: a growing number of octogenarians or older patients are being admitted to the intensive care unit (ICU). The aim of this study was to assess factors associated with acute renal replacement therapy (ARRT) requirement in these patients and the impact of ARRT on the 90-day ICU mortality. Also we aimed to identify prognostic factors associated with mortality risk in the group of patients that required ARRT. Method: retrospective study of octogenarian or older patients admitted to the ICUs of Hospital Clínic de Barcelona from June 2007 to April 2019. Patients on chronic dialysis treatment or kidney transplant, and patients with limitation of therapeutic support or admitted for less than 48 hours were excluded. Results: 217 patients were included in the study, of which 36.4% required ARRT. Use of vasoactive drugs and Sequential Organ Failure Assessment (SOFA) score on admission were higher in ARRT patients (p=0.009 and <0.001). Basal estimated glomerular filtration rate (eGFR) was lower in the ARRT cohort (p<0.001). Hospital and ICU length of stay were longer in the ARRT cohort (p<0.001). Ninety-day mortality was 58.2% in the ARRT cohort and 55.8% in the control cohort, without statistical differences. In the survival analysis, only female sex and non-renal SOFA ≥6.5 were significantly associated with mortality (p= 0.005 and 0.002 respectively) in the ARRT cohort. Conclusion: mortality was not significatively increased in the octogenarian population that required and got ARRT respect to those who did not require it. Scores like SOFA can help in the process of decision making about initiation of ARRT.